Psychological status of infertile patients who had in vitro fertilization treatment interrupted or postponed due to COVID-19 pandemic: a cross-sectional study - Barra, Fabio; La Rosa, Valentina Lucia; Vitale, Salvatore Giovanni; Commodari, Elena; Altieri, Michele; Scala, Carolina; Ferrero, Simone (Journal of psychosomatic obstetrics and gynaecology, 2022)
To explore the psychological status of infertile women and men who had in-vitro fertilization (IVF) treatment interrupted or postponed because of the COVID-19 emergency. An electronic survey (NCT04395755) was e-mailed between April and June 2020 to couples whose IVF treatments have been interrupted or postponed due to the COVID-19 pandemic. The presence and severity of symptoms suggestive of anxiety and/or depression were assessed using the Generalized Anxiety Disorder-7 (GAD-7) and the Patient Health Questionnaire-9 (PHQ-9). Subjects with preexisting psychiatric disorders were excluded. Overall, 524 out of 646 patients completed the survey. The prevalence of anxiety and/or depression feelings was significantly higher in women, mainly if aged more than 35 years and with a previous IVF attempt. The occurrence of these psychological symptoms was significantly associated with the time spent on COVID-19 related news per day and partner with evidence of psychological disorder and, in females, with a diagnosis of poor ovarian reserve, diagnosis of endometriosis or uterine fibroids. The psychological impact of the COVID-19 pandemic on the infertile couples who should have undergone IVF treatment has been significant. IVF centers should systematically offer these couples adequate psychological counseling to improve mental health.